An open label study on Depression Patient's Disability Outcomes: Comparative Evaluation of Escitalopram and Amisulpride - Kaul, Vijay; Dutta, Shaktibala; Beg, Mirza Atif; Singh, Nand Kishore; Bawa, Shalu; Anjoom, Mohammed; Dutta, Srihari; Rai, Prithi (Journal of Nobel Medical College, 2016)
Background Depression is an important global public health problem due to its relatively high lifetime prevalence and significant disability caused by it. The present study was conducted to compare improvement in disability outcome by Amisulpride and Escitalopram among depression patients using WHO-Disability Assessment Schedule (WHO-DAS).Materials and Methods The study was conducted in depression patients for 1 year in the Department of Neuropsychiatry, Nepalgunj Medical College & Teaching Hospital. A total of 117 depression patients were divided into 2 groups. Group I (58 patients) received Amisulpride tablet at a dose of 50 mg/day and Group II (59 patients) were given Escitalopram at a dose of 10 mg/day. The patients were required to follow up at 4 weeks, 8 weeks and at 15 weeks. The efficacy of the drugs was calculated by Hamilton depression rating scale (HAM-D). The improvement in functional outcome was compared between the two groups by using WHO-Disability Assessment Schedule (WHO-DAS). Appropriate statistical tools using GraphPadInstat 3.0 were used for analysis. p value < 0.05 was considered significant.Results HAM-D score in group receiving Amisulpride at 0 and 15 weeks was 16.92±0.35 and 7.87±0.29 (p